Pengaruh Budaya Lokal terhadap Pelaksanaan Hukum Pidana di Indonesia - Robekha, Jamiatur; Pratama, Anggerdi Adji; Mulya, Musa Alam; Purba, Lilis (PT Elaborium Elevasi Indonesia, 2024)
In the context of criminal law, although there are formal regulations that apply throughout the country, local culture often plays an important role in their implementation. Therefore, understanding the interaction between local culture and the implementation of criminal law in Indonesia is essential to ensure effectiveness and fairness in the legal system.This study applies a qualitative approach, combining literature analysis methods. The information collected is descriptive, both in written and oral form. A legislation-based approach is adopted to collect various relevant laws and regulations, while literature analysis helps in understanding the context of the legal issues discussed.The results show that although official authorities such as the police and courts still play a role, traditional institutions are often the first place for mediation in resolving conflicts, especially those rooted in local issues. This indicates that traditional and cultural values ​​occupy an important place in society and influence how society relates to the formal legal system.